KALIMAT INTEROGATIF BAHASA BATAK TOBA DALAM TURI-TURIAN NI SI JONAHA - Saragi, Wandy; Faizah AR, Hasnah; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe interogative sentences of Batak Toba language which includes (1) types of interogative sentences, (2) markers of interogative sentences. This research is a descriptive research. The subject of this study is the Turi-turian text of Ni Si Jonaha. The object of this study is the interogative sentences contained in Turi-turian Ni Si Jonaha. Data of this study were obtained by reading and recording techniques. The data were analyzed by (1) classifying them based on types and markers of the interrogative sentences (2) analyzing them with reference to the theory used in accordance with the synthesis (3) describing and interpreting them based on the research findings, and (4) writing a report on analysis findings called a project paper. The research findings are as follows; (1) interrogative sentences ask for recognition of